Arabidopsis JAZ Proteins Interact with and Suppress RHD6 Transcription Factor to Regulate Jasmonate-Stimulated Root Hair Development. Issue 4 (27th January 2020) - Han, Xiao; Zhang, Minghui; Yang, Milian; Hu, Yanru
Abstract : JAZ repressors of the jasmonate pathway directly interact with and suppress RHD6 and RSL1 transcription factors to integrate jasmonate signaling and root hair development in Arabidopsis. Abstract: Root hairs arise from trichoblasts and are crucial for plant anchorage, nutrient acquisition, and environmental interactions. The phytohormone jasmonate is known to regulate root hair development in Arabidopsis ( Arabidopsis thaliana ), but little is known about the molecular mechanism underlying jasmonate modulation in this process. Here, we show that the application of exogenous jasmonate significantly stimulated root hair elongation, but, on the contrary, blocking the perception or signaling of jasmonate resulted in defective root hairs. Jasmonate consistently elevated the expression levels of several crucial genes positively involved in root hair growth. Mechanistic investigation revealed that JASMONATE ZIM-DOMAIN (JAZ) proteins, critical repressors of jasmonate signaling, physically interacted with ROOT HAIR DEFECTIVE 6 (RHD6) and RHD6 LIKE1 (RSL1), two transcription factors that are essential for root hair development. JAZ proteins inhibited the transcriptional function of RHD6 and interfered with the interaction of RHD6 with RSL1. Genetic analysis indicated that jasmonate promoted root hair growth in a RHD6/RSL1-dependent manner. Moreover, overexpression of RHD6 largely rescued the root hair defects of JAZ-accumulating plants. Collectively, our study reveals a key signaling module in which JAZ repressors of the jasmonate pathway directly modulate RHD6 and RSL1 transcription factors to integrate jasmonate signaling and the root hair developmental process.